Exclusion and the growth of AI technology: a trade-theoretic analysis - Hazari, Bharat; Mohan, Vijay (Frontiers in Human Dynamics, 2024)
This paper provides a four-good general equilibrium framework with international trade for assessing the impact of an advancement of automation and artificial intelligence (A&AI) on the welfare of a group of agents who are excluded both from owning productive assets, such as capital and land, as well from consuming digital output (digital exclusion). We show that, depending on magnitude of the factor intensities, the accumulation of A&AI capital may negatively affect the income of either the excluded group who provide unskilled labor, or the owners of land. In doing so, we bring out the conflict of interests that may arise between the owners of A&AI capital and other groups within society, which has implications for the pressures that exist to slow down the adoption of A&AI in an economy.